2017
DOI: 10.1039/c7dt02989f
|View full text |Cite
|
Sign up to set email alerts
|

A new {Fe4Co4} soluble switchable nanomagnet encapsulating Cs+: enhancing the stability and redox flexibility and tuning the photomagnetic effect.

Abstract: We report a new cyanide-bridged Cs⊂{FeCo} box, a soluble model of photomagnetic Prussian blue analogues (PBAs). The Cs ion has a high affinity for the box and can replace the K ion in the preformed K-cube. This exchange is kinetically impeded at room temperature but is accelerated by heating and using the 18-crown-6 ether. The inserted Cs ion confers a high robustness to the cube, which withstands boiling, as shown by variable-temperature NMR studies. The stability of this model complex in solution allows the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
49
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 39 publications
7
49
1
Order By: Relevance
“…The strong and negative paramagnetic chemical shift is due to the spin-density transfer from the paramagnetic cage to the intercalated Cs + ion, as already observed in related systems. [24] The addition of CsClO 4 salt to the solution allows confirming this assignment, as it leads to the occurrence of a new signal in the diamagnetic range at 32 ppm.…”
mentioning
confidence: 77%
See 4 more Smart Citations
“…The strong and negative paramagnetic chemical shift is due to the spin-density transfer from the paramagnetic cage to the intercalated Cs + ion, as already observed in related systems. [24] The addition of CsClO 4 salt to the solution allows confirming this assignment, as it leads to the occurrence of a new signal in the diamagnetic range at 32 ppm.…”
mentioning
confidence: 77%
“…In particular, we demonstrated that the encapsulation of a Cs + ion within the anionic {Co 4 Fe 4 } cube causes the entire complex to be remarkably stable. [21] Similar A&{Ni 4 Fe 4 } cubes could also be obtained by following a similar synthetic strategy. [22] Our present work intends to extend these results toward other switchable molecules that could show interesting properties such as electro-, thermo-, or photo-induced switching of the electronic states.…”
mentioning
confidence: 86%
See 3 more Smart Citations